Population pharmacokinetics for oral paclitaxel in patients with advanced/metastatic solid tumors - Jimmy He; Christopher G. C. A. Jackson; Sanjeev Deva; Tak Hung; Katriona Clarke; Eva Segelov; Tsu‐Yi Chao; Ming‐Shen Dai; Hsien‐Tang Yeh; Wen Wee Ma; Douglas Kramer; Wing‐Kai Chan; et al. (Wiley, 2022)
Abstract Oraxol consists of an oral dosage form of the chemotherapeutic agent paclitaxel administered with a novel P‐glycoprotein inhibitor encequidar methanesulfonate monohydrate (formerly named HM30181A), which allows oral treatment of cancers that would otherwise be treated with intravenous paclitaxel. Here we describe the population pharmacokinetics (popPK) analyses for oral paclitaxel in patients with advanced/metastatic solid tumors to characterize pharmacokinetic (PK) profiles and quantify sources of PK variability. The best fit popPK model for oral paclitaxel, based on data from seven clinical studies (197 patients with advanced/metastatic solid tumors), involves a linear two‐compartment structural model containing first‐order absorption with a short lag time and first‐order elimination as well as a log additive error. In this popPK model, lower population estimates of central volume for Asian patients versus Caucasian patients did not translate into clinical meaningful differences in oral paclitaxel exposure. Age, sex, body weight or surface area, mild hepatic impairment, and mild to moderate renal impairment had no clinically meaningful effects on the systemic exposure of oral paclitaxel. Simulations were performed on clinical therapeutic dose (oral paclitaxel 205 mg/m2 once daily ×3 days per week) to predict exposure of oral paclitaxel and to support treatment benefits observed in a pivotal phase III trial.